The role of the head of room in supervising the icu room of Sembiring Delitua general hospital - Johannes Sembiring; Elmina Tampubolon (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Nursing services are a sub-system in health services in hospitals, of course they have an interest in maintaining service quality, moreover, nursing services are often used as a benchmark for the image of a hospital so that it demands the professionalism of implementing nurses and managing nurses. Optimal contribution in realizing quality health services is carried out through the leadership style of the head of the room. The leadership style carried out by the head of the room will have a close impact on the nurse's performance. The formulation of the problem in this research is how is the role of the head of the room in supervising the ICU room at the Sembiring Delitua General Hospital?. The data obtained through interviews with the results of the analysis using the Triangulation method can be concluded: Input (HR), Process (knowledge, skills and leadership), Output (democratic leadership style) carried out on informants. The results in this study that the leadership in the ICU room is good because the head of the room applies democratic leadership. Abstrak: Pelayanan keperawatan merupakan sub sistem dalam pelayanan kesehatan di rumah sakit sudah pasti punya kepentingan untuk menjaga mutu pelayanan, terlebih lagi pelayanan keperawatan sering dijadikan tolak ukur citra sebuah rumah sakitsehingga menuntut adanya profesionalisme perawat pelaksana maupun perawat pengelola. Kontribusi yang optimal dalam mewujudkan pelayanan kesehatan yang berkualitas dilakukan melalui gaya kepemimpinan kepala ruangan. Gaya kepemimpinan yang dilakukan kepala ruangan akan berdampak erat dengan kinerja perawat. Rumusan masalah dalam penelitian adalah bagaimana peran kepala ruangan dalam melakukan supervisi di ruang ICU Rumah Sakit Umum Sembiring Delitua. Data diperoleh melalui wawancara dengan hasil analisis dengan metode Triangulasi dapat disimpulkan: Input (SDM), Process (adanya pengetahuan, keterampilan dan leadership), Output (gaya kepemimpinan yang demokratis) yang dilakukan pada informan. Hasil dalam penelitian ini bahwa kepemimpinan di ruang ICU baik dikarenakan kepala ruangan menerapkan kepemimpinan demokratis.